2021
DOI: 10.1155/2021/4475184
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Synchronization Type and Degree in Respiratory Neural Network

Abstract: Pre-Bötzinger complex (PBC) is a necessary condition for the generation of respiratory rhythm. Due to the existence of synaptic gaps, delay plays a key role in the synchronous operation of coupled neurons. In this study, the relationship between synchronization and correlation degree is established for the first time by using ISI bifurcation and correlation coefficient, and the relationship between synchronization and correlation degree is discussed under the conditions of no delay, symmetric delay, and asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Studies have shown that tens of thousands of neurons exist within the cerebral cortex approximately per cubic millimeter, with a total of approximately more than 10 billion neurons combining with each other to form vast neuronal networks. Synchronization in neuronal networks [1], a complex pattern of population firing, is thought to play a key role in many brain functions and many basic biological functions. For example, it has been associated with sensory processing [2], sleep rhythm generation [3], Parkinson's tremor [4], and seizures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that tens of thousands of neurons exist within the cerebral cortex approximately per cubic millimeter, with a total of approximately more than 10 billion neurons combining with each other to form vast neuronal networks. Synchronization in neuronal networks [1], a complex pattern of population firing, is thought to play a key role in many brain functions and many basic biological functions. For example, it has been associated with sensory processing [2], sleep rhythm generation [3], Parkinson's tremor [4], and seizures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, time delays are observed in most biological systems. Due to the existence of synaptic gaps, delay plays a key role in the synchronous operation of coupled neurons [ 25 ]. The finite transmission speed of the membrane potential along the neurons' axons and time gaps due to synaptic (information transmission) and dendritic (reception) processes between neurons produce time delays in neuronal communications [ 26 ].…”
Section: Introductionmentioning
confidence: 99%